PAT-8 Antiproliferation Activity of Keladi Tikus (Typhonium flagelliforme) Leaves Ethanol Extract on MCA- B1 and MCM-B2 Tumor – Derived Cell Lines In Vitro - Riski Rostantinata; Bambang Pontjo Priosoeryanto; Eva Harlina; Waras Nurcholis; Lina Noviyanti; Rachmi Ridho (Hemera Zoa, 2018)
INTRODUCTIONTumor is a degenerative disease as the second agent cause of death in human. This disease is caused by disturbances of cell’s growth that show alteration and uncontrolled of cells proliferation. The uncontrolled of cells proliferation is also accompanied by penetration of that cells into others tissue and develop on it. Removed of tumor is usually done by operation or chemotherapy. Alternative treatment that can be used is herbal treatment. Typhonium flagelliforme known as “Keladi Tikus” in Indonesia; is known has a chemopreventive effect (2). Other researchers also show flavonoid glucoside of T. flagelliforme (1) can induce the activity of apoptosis in colon cancer cells (5). The aim of this study is to examine the in vitro anti-proliferation activity of Typhonium flagelliforme leaves ethanol extract on MCA- B1and MCM-B2 cell line.